Affordances for manipulation of physical versus digital media on interactive surfaces - Kirk, David; Sellen, Abigail; Izadi, Shahram (Proceedings of CHI Conference on Human Factors in Computing Systems, 2007)
This work presents the results of a comparative study in which we investigate the ways manipulation of physical versus digital media are fundamentally different from one another. Participants carried out both a puzzle task and a photo sorting task in two different modes: in a physical 3-dimensional space and on a multi-touch, interactive tabletop in which the digital items resembled their physical counterparts in terms of appearance and behavior. By observing the interaction behaviors of 12 participants, we explore the main differences and discuss what this means for designing interactive surfaces which use aspects of the physical world as a design resource.